Micro study in building maintenance / Zuraida Yahya - Yahya, Zuraida (1987)
Building Maintenance starts the day the buider leaves the site. Design, materials, workmanship, function, use, safety and their interrelationship, will determine the amount of maintenance required during the life span of the building. Initial cost of building continue to rise year after year and it is becoming very important to maintain the • present standing buildings to the best standard possible. To achieve this goal, effective maintenance plays an important role, besides appreciation from the community user themselves. Micro study in building maintenance deals with the sources that leads to the existence of building maintenance, revealing the common problems and suggesting solutions. Emphasis is given to the academic buildings at MARA Institute of Technology, Shah Alam with case study on the School of Architecture, Planning and Surveying. It has been brought up that the maintenance of the school has not reached the schools desired standard ever since its establishment in the year 1967* No research has yet been carried out in this problem. Hence it is the objective of this dissertation to study into the problems and work out solutions and recommendation in relation to the building structures an& facilities, building user and; the construction industry Designer, Builder and Maintenance organisation. It is the aim of the aim of the study to develop a better learning condition and upgraded maintenance standard within the governing policy and available resources to the academic buildings of MIT to form one of the factors contributing to the achievement of high productivity and best quality graduates from MIT as a whole.